Advantages of Using Intraoral Scanner in Prosthodontic Dentistry - Tamar Dolidze; Marika Kublashvili; Mariam Iantbelidze (European Scientific Journal, ESJ, 2025)
Digital dentistry holds a leading role in modern dentistry. Its development perfected dental service, simplified difficult clinical cases and created an opportunity for dentists to be fully involved in a treatment process. The ability to create 3D digital designs, including smile design, increases patient engagement and ensures treatment satisfaction. Using scanners in everyday practice enhances communication between dentists and technical laboratories. This review explores the technical aspects of intraoral scanners, highlighting their key components, such as the mirror, lens, and scanning depth, as well as their advantages over traditional methods. Currently, there are many types of intraoral scanners on the market which differ from each other by their shape, design, price, and functional capabilities. Intraoral scanners are particularly beneficial in cases involving dental implants, as scan bodies facilitate precise digital impressions.  The choice depends on the doctor’s needs and preferences, as well as the area of its use. This study shows the advantages of using intraoral scanners in prosthodontics dentistry, its priorities, and the nuances of their use. In conclusion, intraoral scanners have become an invaluable tool in modern prosthodontics, enhancing treatment quality, efficiency, and patient comfort.